Assessment of the exposure to Phlebotomus perniciosus and the presence of anti-Leishmania infantum antibodies in stray cats in an endemic region of Spain, and their potential correlation with environmental factors (2024)
Phlebotomus perniciosus is a major vector of Leishmania infantum in the Mediterranean. While the seroprevalence of leishmaniosis in Spanish dogs and cats has been studied, data on the exposure of cats to P. perniciosus bites under natural conditions without repellents is limited. Stray cats could serve as sentinels for L. infantum and P. perniciosus exposure. This study analyzed sera from 204 apparently healthy stray cats, collected from January 2021 to January 2022, for antibodies against P. perniciosus saliva and L. infantum parasites. Anti-sand fly antibodies were detected in 40.69% of cats using an ELISA with the recombinant salivary protein SP03B of P. perniciosus. Seroprevalence of L. infantum infection was 23.52% by Western blot and 27.41% by ELISA, with an overall seroprevalence of 40.69% (95% CI 34.18-47.54%). This is the first assessment of antibody response to P. perniciosus saliva and L. infantum in naturally exposed stray cats in Spain. Further research is needed to examine the salivary antigens recognized by cats and to explore the relationship between P. perniciosus exposure and L. infantum infection severity in cats.